Theory of Communotion and the Evolution of Chinese Syntactic Properties - Dai, Zhongxin (Advances in Social Sciences Research Journal, 2019)
The unique syntactic properties of the Chinese language have been universally discussed among Chinese linguists, but the genotypic source of the properties has rarely been explored. This article attempted to explore the source from human communicative notion (communotion). Communotion is the intended notion emerging in the interlocutor’s mind in the context of communication, and impelling him to struggle to express with whatever tool is available. The syntactic properties of human particular languages have evolved from the immanent relationships between the elements in the communotion. This article identifies five design principles underlying the heterogeneous transduction from the hierarchical notional relationships in the communotion to the hierarchical syntactic structures in the Chinese language: Situatedness, Theme Depiction, Dynamic Focalization, Phrase-based Construction and Word Order. The incongruity between the syntactic properties of the Chinese language and other languages is caused by the diversity of the sociocultural conventional verbalization in the realization of the expression of the communotion.